Modeling Asian Dust Storms Using WRF‐Chem During the DRAGON‐Asia Field Campaign in April 2012. Issue 18 (10th September 2021) - Kim, Kyoung‐Min; Kim, Si‐Wan; Choi, Myungje; Kim, Mijin; Kim, Jhoon; Shin, Inchul; Kim, Jeongeun; Chung, Chu‐Yong; Yeo, Huidong; Kim, Sang‐Woo; Joo, Seung Jin; McKeen, Stuart A.; et al.
Abstract: Asian mineral dust substantially influences air quality as well as weather and climate. It is important to forecast dust storms as a part of air quality modeling to protect public health and minimize the disruption to essential daily routines. In this study, we simulated the dust episodes during the DRAGON‐NE Asia field campaign in April 2012 utilizing the Weather Research and Forecasting model coupled with chemistry (WRF‐Chem) with 5 dust emission options and evaluated the model results with the measurements from multiple instruments including Korean geostationary satellites Geostationary Ocean Color Imager (GOCI) and Meteorological Imager (MI). The model well predicted the dust occurrences, transport, and vertically elevated structure, compared to the satellite aerosol optical depths (AOD), the Aerosol Robotic Network (AERONET) AOD and size distribution parameter Angstrom Exponent (AE), the ground‐based lidar and in‐situ observations. However, the model dust concentration varied depending on the selected dust emission option. The model also did not accurately simulate both AOD and AE. When the model AOD agreed with the AERONET AOD, AE did not agree. In general, the model concentrations were overestimated for large size particles (diameter 6–20 μm) and were underestimated for small size particles (0.5–3.6 μm), compared to the observed aerosol size distributions at surface in Korean Peninsula. Our analysis of the episode suggests that the dust is possibly mixed with the aerosols of anthropogenic origins in the Asian region. Therefore, accurate simulations of both anthropogenic aerosols and dust are helpful for evaluating models in the downwind region of the dust sources. Key Points: Asian dust storms in April 2012 were simulated with the weather research and forecasting (WRF)‐Chem five dust emission options The model remarkably reproduced the observed elevated dust layers in the Yellow Sea and South Korea The model could not accurately simulate Angstrom Exponent and Aerosol Optical Depth at the same time